2020
DOI: 10.1002/cam4.3459
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of bone metastasis predict bone‐predominant status to benefit from radium‐223 dichloride for patients with castration‐resistant prostate cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…While there have been many reports on patients treated with Ra‐223 in Japan, none have described the improvement in the OS with Ra‐223 compared with a cohort not treated with Ra‐223 (Table 2). 5–12 Therefore, in the present study, we investigated whether or not Ra‐223 improves the OS in Japanese patients using a large‐scale healthcare fee database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been many reports on patients treated with Ra‐223 in Japan, none have described the improvement in the OS with Ra‐223 compared with a cohort not treated with Ra‐223 (Table 2). 5–12 Therefore, in the present study, we investigated whether or not Ra‐223 improves the OS in Japanese patients using a large‐scale healthcare fee database.…”
Section: Discussionmentioning
confidence: 99%
“…Ra‐223 is widely used in daily clinical practice in Japan for bone metastatic CRPC, with a total of 5852 vials administered annually in 2018 4 . There were several studies to confirm that completion of six‐course Ra‐223 showed longer survival compared to the one‐ to five‐course group and examined the factors who showed longer prognosis who received Ra‐223 in Japanese patients 5–14 . However, almost all studies of Ra‐223 from Japan have used patient cohorts receiving Ra‐223, with no non‐Ra‐223 induction patient cohorts included 2,5,7,10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing clinical experience with Ra-223 given to mCRPC patients, clinical variables useful for predicting response to that radiopharmaceutical and also survival remain di cult to identify. Scoring systems reported include baseline Eastern Cooperative Oncology Group (ECOG) performance status, levels of hemoglobin, alkaline phosphatase (ALP), lactate dehydrogenase (LDH), and prostate speci c antigen (PSA), PSA doubling time (PSADT), completion of six cycles of Ra-223, as well as other factors [5][6][7][8][9][10][11][12][13][14][15]. However, a validated and simple model for clinicians to assess which patients will most likely bene t from Ra-223 treatment remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, Ra-223 was established as a standard treatment modality for mCRPC patients with predominant bone disease and no visceral metastases [4][5][6]. The approved regimen of Ra-223 is an intravenous injection of 55 kBq/kg of Ra-223, every 4 weeks (q4w), for six cycles [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…The biological effectiveness of a radionuclide therapy is dose-dependent [7]. Saad et al conducted a phase IIIb, single-arm study in the setting of an international early access program (iEAP) [8] that evaluated the correlation between the number of treatment cycles of Ra-223 (1-4 vs. [5][6] and the OS using a post hoc analysis [7]. The primary endpoints of this study were the safety and survival of patients treated with Ra-223 for symptomatic or asymptomatic mCRPC.…”
Section: Introductionmentioning
confidence: 99%